2019
DOI: 10.1177/0748730419836370
|View full text |Cite
|
Sign up to set email alerts
|

Casein Kinase 1 Underlies Temperature Compensation of Circadian Rhythms in Human Red Blood Cells

Abstract: Temperature compensation and period determination by casein kinase 1 (CK1) are conserved features of eukaryotic circadian rhythms, whereas the clock gene transcription factors that facilitate daily gene expression rhythms differ between phylogenetic kingdoms. Human red blood cells (RBCs) exhibit temperature-compensated circadian rhythms, which, because RBCs lack nuclei, must occur in the absence of a circadian transcription-translation feedback loop. We tested whether period determination and temperature compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 58 publications
4
34
0
Order By: Relevance
“…In this context, CK1δ/ε frequently operates in tandem with glycogen synthase kinase (GSK) 3α/β, as occurs in the regulation of β‐catenin stability (O’Neill et al , 2013; Robertson et al , 2018). Interestingly, both CK1δ/ε and GSK3α/β have a conserved role in determining the speed at which the eukaryotic cellular circadian clock runs (Hastings et al , 2008; Causton et al , 2015), both in the presence and absence of transcription (Hirota et al , 2008; Meng et al , 2008; O’Neill et al , 2011; Beale et al , 2019). This is despite the fact that the clock proteins phosphorylated by these kinases are highly dissimilar between animals, plants and fungi (Causton et al , 2015; Wong & O’Neill, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, CK1δ/ε frequently operates in tandem with glycogen synthase kinase (GSK) 3α/β, as occurs in the regulation of β‐catenin stability (O’Neill et al , 2013; Robertson et al , 2018). Interestingly, both CK1δ/ε and GSK3α/β have a conserved role in determining the speed at which the eukaryotic cellular circadian clock runs (Hastings et al , 2008; Causton et al , 2015), both in the presence and absence of transcription (Hirota et al , 2008; Meng et al , 2008; O’Neill et al , 2011; Beale et al , 2019). This is despite the fact that the clock proteins phosphorylated by these kinases are highly dissimilar between animals, plants and fungi (Causton et al , 2015; Wong & O’Neill, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that this surface component could be significantly larger than the conventional whole-cell parameter, particularly for smaller cells, making it difficult to extract the membrane conductance parameter. However, this can still be used as an effective discriminator of cellular properties and has been used to detect changes in RBC membrane properties due to malarial infection 49 , as well as identifying circadian rhythms in RBC electrophysiology 25,26 . For Jurkat cells a value of 11.3 nS (equivalent to a specific membrane resistance of 0.45 kΩ.cm 2 ) was obtained which is larger than common values of whole-cell conductance reported for other cell types of similar origin by patch-clamp, though by less than an order of magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…DEP has been used to measure electrical properties of excitable cells and benchmarks well against other, validated methods 18 . DEP-spectra have also successfully defined biomarkers for stem cell differentiation 5,19 , cancer 20,21 , drug interactions 2224 and circadian biology 25,26 . However, although DEP is most effective for measuring cell electrical properties, its adoption as a method in general cell biology has been limited by electrode technology and the challenges associated with robust data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps most intriguing, this difference was found to be a function of, Raman spectroscopy confirmed, membrane morphology and composition differences rather than cell size [128]. Our group also demonstrated DEP's corroboration with FACS and inductively coupled plasma mass spectrometry (ICPMS) in the investigations of circadian rhythms in RBCs [126, 129]. Adams et al demonstrated that one particular DEP‐based cell sorter, Dielectrophoresis assisted continuous sorter (DACS), had even better NP enrichment than FACS of neuron NPs [86–87].…”
Section: Dep Characterization Methods and Parametersmentioning
confidence: 80%